2017
DOI: 10.1111/joor.12520
|View full text |Cite
|
Sign up to set email alerts
|

Validity of different tools to assess sleep bruxism: a meta‐analysis

Abstract: This systematic review and meta-analysis (MA) aimed to evaluate the diagnostic validity of questionnaires, clinical assessment and portable diagnostic devices compared to the reference standard method polysomnography (PSG) in assessing sleep bruxism (SB). Two reviewers searched electronic databases for diagnostic test accuracy studies that compared questionnaires, clinical assessment or portable diagnostic devices for SB, with the reference standard method PSG, comprising previous studies from all languages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 27 publications
2
78
0
1
Order By: Relevance
“…Self‐report of SB may also have influenced the results, and none of the included studies assessed SB through PSG. A preliminary study indicated high sensitivity but low specify of self‐report SB comparing with PSG assessment criteria and a recent systematic review indicated that questionnaires and the clinical assessment are not fully reliable in identifying subjects with SB . Per reasons listed above, heterogeneous results observed due to probable bruxism detection might not be sufficiently reliable for an association assessment between SB and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐report of SB may also have influenced the results, and none of the included studies assessed SB through PSG. A preliminary study indicated high sensitivity but low specify of self‐report SB comparing with PSG assessment criteria and a recent systematic review indicated that questionnaires and the clinical assessment are not fully reliable in identifying subjects with SB . Per reasons listed above, heterogeneous results observed due to probable bruxism detection might not be sufficiently reliable for an association assessment between SB and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This variance may be attributed to fact that the diagnosis of SB in children is still challenging, once it is predominantly accessed through parental report.0 . Other validated methods such as physical examination and/or questionnaires are often used . Although polysomnography is the current reference standard for diagnosing SB, it has some disadvantages, such as high cost and technical difficulties when used in children …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some limitations might be observed in regard to SB symptoms awareness, as individuals who sleep alone or with a sleep partner who is not disturbed by grinding sounds are not able to provide a fully reliable report . In addition, PSG criteria for SB diagnosis might present internal validity problems such as the possibility of night to night variability, and ongoing debates on SB definition and grading may lead to a reappraise of PSG criteria as reference standard …”
Section: Discussionmentioning
confidence: 99%
“…Bruxism may occur during sleep and/or awake state, and as distinct causes and pathophysiology are involved, awake bruxism should be distinguished from the sleep state manifestation of this condition . However, as clinical features distinguishing different forms of bruxism are often misleading, particularly related to sleep bruxism (SB), a polysomnography (PSG) examination is required to fully confirm the diagnosis even though SB is often assessed based on questionnaires and/or physical examination due to costs and availability …”
Section: Introductionmentioning
confidence: 99%